Biosynthesis of DDMP saponins in soybean is regulated by a distinct UDP‐glycosyltransferase. Issue 1 (10th December 2018) - Sundaramoorthy, Jagadeesh; Park, Gyu Tae; Komagamine, Kumpei; Tsukamoto, Chigen; Chang, Jeong Ho; Lee, Jeong‐Dong; Kim, Jeong Hoe; Seo, Hak Soo; Song, Jong Tae
Summary: 2, 3‐Dihydro‐2, 5‐dihydroxy‐6‐methyl‐4 H ‐pyran‐4‐one (DDMP) saponins are one of the major saponin groups that are widely distributed in legumes such as pea, barrel medic, chickpea, and soybean. The steps involved in DDMP saponin biosynthesis remain uncharacterized at the molecular level. We isolated two recessive mutants that lack DDMP saponins from an ethyl methanesulfonate‐induced mutant population of soybean cultivar Pungsannamul. Segregation analysis showed that the production of DDMP saponins is controlled by a single locus, named Sg‐9 . The locus was physically mapped to a 130‐kb region on chromosome 16. Nucleotide sequence analysis of candidate genes in the region revealed that each mutant has a single‐nucleotide polymorphism in the Glyma.16G033700 encoding a UDP‐glycosyltransferase UGT73B4. Enzyme assays and mass spectrum‐coupled chromatographic analysis reveal that the Sg‐9 protein has glycosyltransferase activity, converting sapogenins and group B saponins to glycosylated products, and that mutant proteins had only partial activities. The tissue‐specific expression profile of Sg‐9 matches the accumulation pattern of DDMP saponins. This is the first report on a new gene and its function in the biosynthesis of DDMP saponins. Our findings indicate that Sg‐9 encodes a putative DDMP transferase that plays a critical role in the biosynthesis of DDMP saponins.